(untitled) (REMUNOM, 2025)
The discussion surrounding inheritance law in stable unions gained relevance after the promulgation of the 2002 Civil Code, which generated debates about the constitutionality of the treatment given to the surviving partner in comparison to the spouse. Since then, the Brazilian legal landscape has changed with the aim of equalizing these relationships in the context of succession. The article addresses the unconstitutionality of article 1,790 of the 2002 Civil Code, which established a different succession regime for partners in a stable union compared to spouses. This axiom restricted the inheritance rights of partners, limiting them to assets acquired costly during the stable union, in contrast to the regime applicable to spouses, which covered all assets. This differentiation was considered unconstitutional, as it represented deficient protection and a setback in relation to the rights guaranteed by previous legislation, such as Laws Nos. 8,971/94 and 9,278/96. With the decision, the STF determined the application of the succession regime provided for in article 1,829 of the Civil Code, both for spouses and partners, equalizing the rights between both family entities.